(untitled) (Web of Teachers: Inderscience Research, 2024)
In the study of mountain plant ecology, we consider the special adaptations, ecological interactions, and conservation issues that define this mountain environment. By understanding the complex relationships between mountain plants and their environment, we can gain a deeper understanding of the resilience and diversity of these amazing botanical wonders.